A distribuição do filme brasileiro em salas de cinema - Ramalho, Andréia (2016)
This study is an analysis of the strategies for the public exhibition of Brazilian films released between 2002 and 2014, following the creation of the Brazilian National Agency for the Cinema (ANCINE). The goal is to study the commercial prospects of Brazilian films with the emergence of new technologies highlighting the political and economic backdrop, and to evaluate the measures adopted for funding, regulation and incentives for distribution. The core of the study is made up of two business models for the release of feature-length films directed by José Padilha: Elite Squad (Tropa de Elite) (2007), distributed by Universal Pictures do Brasil, and Elite Squad 2: The Enemy Within (Tropa de Elite 2: o inimigo agora é outro) (2010), which were commercialized independently by the producer Zazen Produções. This study made use of bibliographical, documentary and field research, including the following activities: the reading of literary works, data searches in the Brazilian Yearbook of Cinema and Audiovisual Arts (OCA), in the web portal Filme B and in specialized journals and interviews with the distributors of these films. From a theoretical point of view, it draws on the work of Paulo Emilio Salles Gomes, Ismail Xavier and Arthur Autran, amongst other scholars of the Brazilian cinema and its peculiarities, emphasizing the question of distribution as a fundamental link between cinematographic production and exhibition